Démarche d'investigation, pédagogie transmissive et principe d'autorité : l'exemple du système héliocentrique - Estelle Blanquet; Éric Picholle (Recherches en Éducation)
“Doing science” involves belonging to a community and consenting to the knowledge established by others ; but il also involves questioning it to better actualizing it.The article questions the dual relationship with authority that allows to build the investigative approach. The question of heliocentrism constitutes a striking example of the difficulty to emancipate oneself from the paradigmatic pressure of the dominant culture. A traditional astronomy sequence centered on purely physical skills appears ineffective to overcome the naive Copernicanism of participants. Its association with a sequence specifically designed to legitimize unusual viewpoints allows 30-50 % of students to access the Galilean (ie relativistic) paradigm. The analysis and assessment of the evolution of the participants' relationship to authority show that, beyond its interest in science education, IBSE can be a powerful tool to become aware of the nature of the most established prejudices of the dominant culture, and therefore to emancipate oneself from them.